A Quantitative Study on the Impact of Online Learning on Reading Comprehension Skills - Ahmed El Haddad, Ranya (2023)
This quantitative study aims to investigate the relationship between e education and reading comprehension skills acquisition. It also examines if the previous relationship may impact students’ results in the exams. It also analyses the relationship between students’ knowledge in ICT and their perception and accep tance of online education. To collect data, A survey was sent to students to measure their perception of and satisfaction with online learning. Moreover, the marks of 105 students in an on-campus test were compared to the marks of another one they did online during the pandemic. The study agreed with the previous studies that e learning can impact the reading skills positively and that students are getting aware of its educational benefits. On the other hand, the study did not agree with other studies about students’ knowledge of ICT and how it can positively impact their perception of online education. The study showed that although secondary students have sufficient knowledge of ICT, they do not have positive perceptions of online education.